Phytostimulant properties of highly stable silver nanoparticles obtained with saponin extract from Chenopodium quinoa. (29th June 2020) - Segura, Rodrigo; Vásquez, Gustavo; Colson, Emmanuel; Gerbaux, Pascal; Frischmon, Caroline; Nesic, Aleksandra; García, Danni E; Cabrera‐Barjas, Gustavo
Abstract: BACKGROUND: Quinoa ( Chenopodium quinoa Willd) is an Andean original pseudocereal with high nutritional value. During quinoa processing, large amounts of saponin‐rich husks byproducts are obtained. Quinoa saponins, which are biologically active, could be used for various agriculture purposes. Silver nanoparticles have increasingly attracted attention for the management of crop diseases in agriculture. In this work, silver nanoparticles are synthesized by a sustainable and green method, using quinoa husk saponin extract (QE) to evaluate their potential for application in agriculture as biostimulants. RESULTS: Quinoa extract was obtained and characterized by liquid chromatography with tandem mass spectrometry (LC–MS/MS). Sixteen saponin congeners were successfully identified and quantified. The QE obtained was used as a reducing agent for silver ions to synthesize silver nanoparticles (QEAgNPs) under mild conditions. The morphology, particle size, and stability of Ag nanoparticles were investigated by transmission electron microscopy (TEM), ultraviolet–visible spectroscopy (UV‐visible), energy‐dispersive X‐ray (EDS), zeta potential, and Fourier transform infrared spectroscopy with attenuated total reflection (FTIR‐ATR). Ultraviolet–visible spectroscopy measurements confirmed the formation of silver nanoparticles in the presence of QE, with estimated particle sizes in a range between 5 and 50 nm. According to the zeta potential values, highly stable nanoparticles were formed. The QE and QEAgNPs (200–1000 μg/mL) were also tested in radish seed bioassay to evaluate their phytotoxicity. The seed germination assays revealed that QEAgNPs possessed a phytostimulant effect on radish seeds in a dose‐dependent manner, and no phytotoxicity was observed for both QE and QEAgNPs. CONCLUSION: Silver nanoparticles obtained by a so‐called 'green' method could be considered as good candidates for application in the agricultural sector for seed treatment, or as foliar sprays and plant‐growth‐promoters. © 2020 Society of Chemical Industry